Optimization of Monitoring of Apron Cleanliness from Foreign Object Debris (FOD) by the Apron Movement Control Unit (AMC) at Supadio Pontianak International Airport - Reza Fahlevi Edrus; Awan Awan (CV. Rayyan Dwi Bharata, 2023)
Foreign Object Debris (FOD) is an object or foreign object that is alive or not living in the apron area (aircraft parking area), taxiway and runway (runway) which can cause damage to aircraft and has the potential to pose a hazard to the safety and security of aircraft operations fly. The purpose of this study was to determine the efforts, constraints, and solutions of Apron Movement Control (AMC) officers in monitoring the cleanliness of aprons from Foreign Object Debris (FOD) at Supadio Pontianak International Airport. This study used a qualitative research method using primary and secondary data which was conducted in March 2023 at Supadio Pontianak International Airport. This research was conducted in the Apron Movement Control and Ground Handling units using data collection and retrieval techniques through interviews conducted with 1 resource person from the Apron Movement Control Coordinator, 1 marshaller from PT. Mulio Citra Angkasa as the Ground Handling Agent, through observation, documentation and library research. To test the validity of the data, researchers used credibility, transferability, dependability, and confirmability tests. As for data analysis that researchers use, namely data collection, data reduction, data presentation, verification and conclusions. The results of this study indicate that AMC officers make efforts to monitor the cleanliness of the apron by carrying out scheduled inspections, outside of the scheduled ones, and coordinating with related stake holders such as ground handling, bukaka, and Pertamina. The obstacle faced by AMC officers is the number of officers who are only 2 to 3 people per shift makes it difficult for officers to carry out supervision on the apron, the condition of the apron is cracked, and the construction of new corridors so that it is feared that it can cause FOD to enter the apron. The solution to deal with these obstacles is to carry out routine inspections at least 2 times per shift and additional inspections if the weather is bad, conduct socialization to increase awareness of all stakeholders at the airport, conduct FOD Walks when AMC officers want to operate garbarata.